2003
DOI: 10.1007/s00464-002-8921-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic adjustable gastric banding for massive superobesity ( > 60 body mass index kg/m 2 )

Abstract: Surgery for massive super obesity is a formidable challenge. No existing open or laparoscopic procedure reduces BMI below 30 from a starting point above 55. Laparoscopic adjustable gastric banding has been used to treat 76 massive super obese patients with a BMI > 60 kgs/m2. Median weight was 193 kgs +/-34.7 kgs (154-335 kgs). Five patients had a BMI > 100 kgs/m2. There was neither mortality nor pulmonary emboli. hospital stay was 3 days (1-6 days). Excess weight loss was 46.69 +/-10.5 at 1 year; 59.14 +/- 11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 34 publications
4
28
1
4
Order By: Relevance
“…As proven by recent studies [8,15], other factors, such as BMI and age, influence the final outcome in gastric bypass. For this reason, Fielding [9] advocates performing laparoscopic adjustable gastric banding as a standard technique because it is the simplest technique with the lowest risk, with a mortality rate of 0% in SO patients; however, his oldest patient was only 51 years old.…”
Section: Discussionmentioning
confidence: 97%
“…As proven by recent studies [8,15], other factors, such as BMI and age, influence the final outcome in gastric bypass. For this reason, Fielding [9] advocates performing laparoscopic adjustable gastric banding as a standard technique because it is the simplest technique with the lowest risk, with a mortality rate of 0% in SO patients; however, his oldest patient was only 51 years old.…”
Section: Discussionmentioning
confidence: 97%
“…There was 59% of effective weight loss for laparoscopic adjustable gastric banding at 8 years, and 52% of effective weight loss for Roux-en-Y gastric bypass at 10 years. In another study (Fielding, 2003), weight evolution of obese patients was assessed at 3 and 5 years after laparoscopic adjustable gastric banding, but the weight was not evaluated at 10 years. However, these studies did not emphasize the weight loss results according to the time spent since surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in patients with milder degrees of obesity, procedures that produce greater absolute weight loss may not be advantageous, although this can only regarded as a recommendation by rule of thumb. However, the reverse conclusion, that gastric banding and VBG should not be used in massive obesity, does not seem to fully apply, because recent reports showed that LAGB is associated with sufficient EWL also in patients with a BMI of 60 to 100 (EL 2b [86]; EL 4 [96]). …”
Section: Choice Of Proceduresmentioning
confidence: 92%